Rapidly Proliferating Nodular Fasciitis of the Maxillary Alveolus Extending into Antrum - V Naik; R Kini; A Shetty (Wolters Kluwer Medknow Publications, 2010)
Rapidly growing soft tissue masses of the oral and maxillofacial region are highly diverse in nature and mimic malignancy. Nodular fascidis (NF) being one such lesion. Its aggressive behaviour coupled with nonspecific histological features add to the difficulty in diagnose. NF is a benign, reactive proliferation of fibroblasts (myofibroblasts) in the subcutaneous tissues. They are common in upper extremities, forearm being involved quite frequently: involvement of oral cavity is extremely rare. Although it can occur at any age, it is quite common in 2nd to 4th decades. Both sexes appear equally affected. It presents as rapidly growing soft tissue mass of very short duration, ranging in size from 0.4 to 10.5 cm in diameter. Light microscopy and immunohistochemical examinations are means of confirming the diagnosis definitively. Surgical resection of the lesion is the treatment of choice. We report a case of NF of oral cavity involving maxillary sinus which enlarged alarmingly after an incisional biopsy. Immunohistochemisstry for 'Vimentin' marker was positive and confirmed the diagnosis.